Experimental analysis of a composite thermal wall containing gypsum board and açaí stone residue - Silva Nascimento, Ubiraci; Maria Cruz Nascimento, Sandra; de Vasconcelos Silva, Willian; Sousa Almeida, Alison (Seven Editora, 2023)
Currently, environmental issues are gaining more and more accentuated prominence, since the future of humanity is dependent on the actions taken today by man. Great efforts are being spent in the search for knowledge and sustainable alternative solutions that promote development without compromising the environment. Over time, with the advancement of studies and technology, and in return, with the increase in global temperature, the comfort requirements of the population also increased and comfort levels could only be satisfied at the expense of increased consumption of conventional energy to meet the deficiencies of construction. This situation has resulted in an increase in energy consumption in the residential sector, to obtain good thermal comfort. (FRANCO, 2010) .DOI: https://doi.org/10.56238/devopinterscie-134